A CRITICAL DISCOURSE ON THE RELATIONSHIP BETWEEN SCIENCE, TECHNOLOGY, INNOVATION, AND INTELLECTUAL PROPERTY IN AFRICA (The Pretoria Student Law Review, 2023)
BOOK REVIEW: CB Ncube Science, Technology & Innovation and Intellectual Property: Leveraging Openness for Sustainable Development in Africa (2021) 1st ed 1-213, Juta and Company Ltd, ISBN 978 1 48513 765 8.